Fluctuation in the assimilation of problematic experiences: A comparison of two contrasting cases of Emotion Focused Therapy. (17th November 2021) - Basto, Isabel; Stiles, William B.; Pinheiro, Patrícia; Mendes, Inês; Rijo, Daniel; Salgado, João
Abstract: The assimilation model suggests that therapeutic change occurs through a gradual assimilation of problematic experiences. Previous case studies have suggested that both good- and poor-outcome cases exhibit a fluctuating pattern of assimilation progress, characterized by advances and setbacks. Our study examined more closely how this fluctuating pattern is related to symptom change across therapy. We analyzed the longitudinal relations among assimilation ratings, instability (fluctuation) in assimilation ratings, and clinical symptom intensity in two contrasting cases of emotion-focused therapy for depression, one good and one poor outcome. We used the assimilation of problematic experiences scales (APES) to measure assimilation and the outcome- questionnaire (OQ-10) to measure clinical symptom intensity. To assess assimilation instability, we used a fluctuation measure that calculated the amplitude and the frequency of changes in assimilation levels. The results showed that in the good-outcome case, assimilation levels and instability tended to increase and symptom intensity tended to decrease, particularly in the final phase of treatment. In the poor-outcome case, assimilation levels and instability did not change much across sessions.